Evaluating Student’s Usage and Satisfaction of E-Learning Management System: A Perspective of Students from Different Discipline Programmes - Al-Shawabkeh, Mahmoud; Yaidi Toklubok, Mamad; Ghazali, Mazlinah; Hamedon, Siti Rihimi; Rusli, Nazreen; Sulaiman, Hafisah (2012)
The ongoing advancement of technology in universities is promoting the use of E-learning management system during learning process. E-Learning management system has been introduced and used at International Islamic University Malaysia IIUM for more than five years. Trainings on E-learning has been conducted to both students and lecturers and supporting user guides can be downloaded from IIUM E-learning site. However, the rate of usage of E-learning management system at the Centre for Foundation Studies CFS is still very low and students’ satisfaction of the system was never explored. Prior research has provided valuable insights into how and why students make a decision about the adoption and use of E-Learning management system in the university. There is limited research in the IT implementation literature that deals with the role of Computer Self-Efficacy (CSE) to aid such student’s interventions. Particularly, there is a need to understand how various students’ disciplines can influence the known determinants of E-learning usage and user satisfaction. This paper is part of an ongoing research project designed to measure the E-learning system usage and user satisfaction with a view to adapting the instrument developed by Technology Acceptance model (TAM) for use in E-learning environment. It also built based on the work of DeLone and McLean IS Success Model by examining the important role of System Quality and Information Quality leading to system actual use and user satisfaction. The study will employ literature review and interview method to reveal factors that influence the E-learning usage and user satisfaction of foundation level students from various disciplines. The paper intends to develop a comprehensive model of the determinants of student’s level (E-learning) usage and satisfaction.